Außenpolitik nach der Kuba-Krise (Dezember 1962 bis Oktober 1964) - Wettig, Gerhard (Quellen und Darstellungen zur Zeitgeschichte, 2016)
After the Cuban Missile Crisis, Khrushchev exercised more prudence and adopted a long-term perspective on furthering his goal of expelling the Western powers from Berlin and rendering a major defeat to NATO. Adenauer`s retirement left him hoping for a change of course in West German policy. Neither goal was truly based in reality. Overall, Khrushchev`s over-ambitious Western policy remained unsuccessful, despite his efforts.